The Bahasa Indonesia Vocabulary Acquisition on a Five-Year-Old Refugee - Lilis Sulistyowati; Fahriany Fahriany; Nurhalimah Nurhalimah (Jurusan PGMI FTIK IAIN Metro Lampung, 2019)
Abstract The paper attempts to answer the questions on the total of Bahasa Indonesia vocabulary that MazenAbdu Daud has acquired and mastered from the first time he has been following the preparation class for almost four months. This is a qualitative study. It is conducted in a UNHCR’s learning center in Ciputat, Jakarta. It has been seen as potentially significant for some main reasons. First, this study draws attention to give an understanding about forced displace person including refugee and asylum seeker. The description of presence needs life and how Bahasa Indonesia is important for them. Second, it offers readers an overview of many refugees in Jakarta Greater area about their country, culture, and history of life. Then, it provides detail information about vocabulary acquisition of Mazen. Concurrently, this study will contribute to give an overview of the refugee education experiences in Indonesia as a transit country, especially who live in Jakarta Greater area. And the last, this study offers unique insight into how refugees adapt to the community in the scope of displacement, marginalization, loneliness, and socialization in the host culture. Such findings will inform teachers, school officials, and policymakers as they consider new ways to assist newly arrived immigrant, including refugees and asylum seekers. This study also contributes to studies on language acquisition process. Keyword: acquisition, refugee, bilingualism, qualitative Abstrak Penelitian ini berupaya menjawab pertanyaan tentang total kosakata Bahasa Indonesia yang diperoleh dan dikuasai Mazen sejak pertama kali mengikuti kelas persiapan selama hampir empat bulan. Penelitian adalah penelitian kualitatif. Penelitian ini dilakukan di pusat pembelajaran UNHCR di Ciputat, Jakarta. Penelitian ini terlihat potensi signifikan untuk beberapa alasan utama. Pertama, penelitian ini menarik perhatian dalam memberikan pemahaman tentang orang yang dipindahkan secara paksa termasuk pengungsi dan pencari suaka. Deskripsi tentang kebutuhan untuk hidup dan bagaimana Bahasa Indonesia berperan penting bagi mereka. Kedua, menawarkan kepada pembaca gambaran dari pengungsi-pengungsi yang tinggal di wilayah Jabodetabek tentang negara, budaya, dan sejarah hidup mereka. Kemudian, penelitian ini memberikan informasi detail tentang akuisisi kosa kata oleh Mazen Abdu Daud. Bersamaan dengan itu, penelitian ini akan berkontribusi untuk memberikan gambaran tentang pengalaman pendidikan pengungsi di Indonesia sebagai negara transit, terutama di wilayah Jabodetabek. Dan yang terakhir, penelitian ini menawarkan wawasan unik tentang bagaimana pengungsi beradaptasi dengan masyarakat dalam lingkup perpindahan, marginalisasi, kesepian, dan sosialisasi dalam budaya tuan rumah. Temuan semacam itu akan memberi informasi kepada guru, pejabat sekolah, serta pembuat kebijakan ketika mereka mempertimbangkan cara-cara baru untuk membantu imigran yang baru tiba, termasuk para pengungsi dan pencari suaka. Studi ini juga berkontribusi pada studi tentang proses akuisisi bahasa. Keyword: pemerolehan, pengungsi, bilingualisme, kualitatif